IMPLEMENTASI LITERASI DIGITAL BERBASIS KAHOOT TERHADAP KEAKTIFAN BELAJAR SISWA DI SDN PANGARANGAN V - Choli Astutik; A Khoesno Shovie; Siti Nurhalizah; Devi Susanti; Jesika Nurdianita S; Syaiful Hasan Wahyudi; Adit Ayyubi Prasetyo; Ahmad Riyan Hidayat; Hasan Bashri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of information and communication technology has brought changes to the learning process in elementary schools, one of which is through the use of digital media. The use of technology-based learning media can be a means to support the implementation of digital literacy while increasing student learning engagement. This study aims to describe the implementation of Kahoot!-based digital literacy and its impact on student learning engagement at SDN Pangarangan V. This study used a qualitative descriptive approach. Data sources consisted of primary and secondary data. Primary data were obtained through interviews with the principal, teachers, and students in grades III, IV, V, and VI, while secondary data came from supporting documents and relevant scientific articles. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data condensation, data presentation, and drawing conclusions. The results show that the implementation of Kahoot!-based digital literacy was carried out through the stages of media introduction, learning implementation, and evaluation. The use of Kahoot! made the learning process more interesting, interactive, and enjoyable, enabling students to be more active in answering questions, discussing, and engaging in learning activities. Furthermore, the use of this media also helps students become familiar with and utilize digital technology as a learning tool. Despite several obstacles, such as limited devices and unstable internet connections, the implementation of Kahoot! still has a positive impact on increasing student learning engagement.